Radiological features of experimental staphylococcal septic arthritis by micro computed tomography scan. - Farah Fatima; Ying Fei; Abukar Ali; Majd Mohammad; Malin C Erlandsson; Maria I Bokarewa; Muhammad Nawaz; Hadi Valadi; Manli Na; Tao Jin (PLoS ONE)
Background Permanent joint dysfunction due to bone destruction occurs in up to 50% of patients with septic arthritis. Recently, imaging technologies such as micro computed tomography (μCT) scan have been widely used for preclinical models of autoimmune joint disorders. However, the radiological features of septic arthritis in mice are still largely unknown. Methods NMRI mice were intravenously or intra-articularly inoculated with S. aureus Newman or LS-1 strain. The radiological and clinical signs of septic arthritis were followed for 10 days using μCT. We assessed the correlations between joint radiological changes and clinical signs, histological changes, and serum levels of cytokines. Results On days 5-7 after intravenous infection, bone destruction verified by μCT became evident in most of the infected joints. Radiological signs of bone destruction were dependent on the bacterial dose. The site most commonly affected by septic arthritis was the distal femur in knees. The bone destruction detected by μCT was positively correlated with histological changes in both local and hematogenous septic arthritis. The serum levels of IL-6 were significantly correlated with the severity of joint destruction. Conclusion μCT is a sensitive method for monitoring disease progression and determining the severity of bone destruction in a mouse model of septic arthritis. IL-6 may be used as a biomarker for bone destruction in septic arthritis.